EFEKTIVITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI BALAI RW (STUDI KASUS KELURAHAN MEDOKAN AYU) - Devi Erlinda Artama Putri; Katerina Bataha (Jurnal PubBis, 2023)
Public service is one of the efforts made by the government to provide services to the public. One of the public service areas offered by the Surabaya City Government is population administration services at the Surabaya City Population and Civil Registration Service. To take care of their population administration, Surabaya residents can come to Medokan Ayu Urban Village and Neighbourhood Hall. This study aims to describe and analyze the effectiveness of population administration services at the Balai RW or Neighbourhood Hall Medokan Ayu Urban Village as  the Surabaya City Population and Civil Registry Office program to bring closer, simplify, and increase public awareness of population administration documents. This research is qualitative research with a case study approach. Data collection was carried out through interviews with three informants who were determined by purposive sampling, observation and documentation. This study refers to the theory of effectiveness, which consists of four indicators: the accuracy of program targets, program socialization, achievement of program objectives, and program monitoring. The results of this study indicate the effectiveness of services at the RW hall there is an increase in the awareness and enthusiasm of citizens in managing population administration documents. Medokan Ayu Urban Village, Neighbourhood Head, and Population and Civil Registry Office of Surabaya City have conducted socialization of the population administration service program at the Neighbourhood Hall. Citizens can easily manage their documents because they are close to where they live, but there are still obstacles in implementing the program. Medokan Ayu Neighbourhood Head and Surabaya City Population and Civil Registry Office have conducted monitoring and evaluation of the population administration service program at the Neighbourhood Hall.